Optimizing operational efficiency and product quality in fashion SMES: a lean manufacturing approach in jeans production - Huaylinos Vicente, Jorge Luis (2024)
This research develops the approval of a production model to improve operational efficiency and product quality by standardizing processes and reducing errors and waste in a company dedicated to the production and sale of jeans in Peru. The model is based on the Lean Manufacturing philosophy and Work Study, structured in four phases: organization of work stations through the 5S methodology, critical analysis of processes, control of the production process through poka-yoke and consolidation of the production process. The results showed an improvement in operational efficiency from 68% to 74%, an increase of 177.08% in the 5S audit and a 50% reduction in the occurrence of errors. In addition, labor productivity increased from 4.6 to 5.2 units per PEN, which represented an improvement of 13.04%. These findings demonstrated the effectiveness of the model in optimizing the jeans production process in SMEs.